Validation of Wound Assessment Instruments Across Brazilian Clinical Contexts: Protocol for a Scoping Review - Clarissa Albuquerque Vaz Nunes; Emerson Roberto dos Santos; João Daniel de Souza Menezes; Matheus Querino da Silva; Leonila Santos de Almeida Sasso; Ana Maria Rita Pedroso Vilela Torres de Carvalho Engel; Giovana Viecili Rossi; Camila Bortoluci de Lima; Janaína Aparecida de Sales Floriano; Pedro Carlos Cagnazzo; Rauer Ferreira Franco; Alana Clara Santos Rocha; et al. (JMIR Research Protocols, 2026)
Abstract Background Wounds are common and clinically consequential, and consistent assessment is essential for communication, monitoring, and decision-making. Although multiple wound assessment instruments exist, there is no agreement among specialists on which criteria to prioritize during validation processes and evidence synthesis remains insufficient within the Brazilian context. Objective This scoping review aims to map which aspects of wound assessment instruments are considered important by expert health professionals when validating these instruments in the Brazilian context across clinical care settings. Methods The review will be conducted in accordance with JBI guidance for scoping reviews. A 3-step search strategy will be used on the MEDLINE (PubMed), Embase, Scopus, Web of Science, and Cochrane Library databases, as well as in the LILACS, SciELO, and BDENF (Base de Dados em Enfermagem) databases, supplemented by gray literature sources (Brazilian Digital Library of Theses and Dissertations, CAPES Theses Catalog, and Google Scholar) and reference list screening. Records will be deduplicated and screened by 2 independent reviewers, with reporting aligned to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. Data will be extracted using a piloted extraction tool and synthesized descriptively in tables and with narrative mapping. Critical appraisal will not be performed. Results This protocol was registered with the Open Science Framework on February 6, 2026. Database searches are scheduled to commence following protocol publication. Data collection is projected to begin in July 2026, with screening and data extraction expected to be completed by December 2026, and the final review report planned to be submitted for publication in the first quarter of 2027. Results will map the extent, nature, and distribution of evidence on expert-led validation of Brazilian wound assessment instruments across clinical settings. Conclusions This scoping review will provide a systematic and transparent synthesis of which aspects health professionals consider when validating Brazilian national wound assessment instruments. We expect the findings to identify methodological gaps, inform future validation studies, and support the development and refinement of nationally applicable instruments across diverse Brazilian health care contexts.